Clinical Practice: Evidence-Based Recommendations for the Treatment of Cervical Dystonia with Botulinum Toxin - Contarino, Maria Fiorella; Van Den Dool, Joost; Balash, Yacov; Bhatia, Kailash; Giladi, Nir; Koelman, Johannes H.; Lokkegaard, Annemette; Marti, Maria J.; Postma, Miranda; Relja, Maja; Skorvanek, Matej; Speelman, Johannes D.; et al. (Frontiers in Neurology, 2017)
Cervical dystonia is the most frequent form of focal dystonia. Symptoms often result in pain and functional disability. Local injections of botulinum neurotoxin are currently the treatment of choice for cervical dystonia. Although this treatment has proven effective and is widely applied worldwide, many issues still remain open in the clinical practice. We performed a systematic review of the literature on botulinum toxin treatment for cervical dystonia based on a question-oriented approach, with the aim to provide practical recommendations for the treating clinicians. Key-questions from the clinical practice were explored. Results suggest that while the beneficial effect of botulinum toxin treatment on different aspects of cervical dystonia is well established, robust evidence is still missing concerning some practical aspects, such as dose-equivalence between different formulations, optimal treatment intervals, treatment approaches, and the use of supportive techniques including electromyography (EMG) or ultrasounds. Established strategies to prevent or manage common side effects (including excessive muscle weakness, pain at injection site, dysphagia) and potential contraindications to this treatment (pregnancy and lactation, use of anticoagulants, neurological comorbidities) should also be further explored.